Silêncio e ausência de sentido: uma análise dos textos produzidos na Oficina de Leitura do Discurso de Editorial - Nichele, Alessandra Ilha; Rodrigues, Daniela Leite (Linguagens & Cidadania, 2017)
This paper aims to present, under the Discourse Analysis (DA) theoretical perspective, the silence which is established in language by the excess whose lack is due to the “too full”. In order to do this, it will be analyzed a corpus of texts written by seventh grade students in a Reading Workshop belonging to the research and extension project called PROLICEN. For this purpose we used, as motivation to textual production, the sample of na editorial from Zero Hora newspaper published in June, 2009. We have tried to identify, in two texts, the silence produced by words that, even having grammaticality, from the syntactic point of view, shows up the incompleteness of sense, and, concerning social issues, the students’ discourse points to a consumerist tendency which overlaps the question of professional qualification.